Subjectivity and Academic Discourse: Apples, Cupcakes, and Beige - Frances Jo Grossman (Journal of the Assembly for Expanded Perspectives on Learning, 1995)
The relationship between intentional autobiographical reference and academic research yields a discourse called the writer-scholar's story of knowing.